Epidemiological aspects of melanoma at a university hospital dermatology center over a period of 20 years* - Brandão, Flavia Vieira (Sociedade Brasileira de Dermatologia, 2013)

(untitled)
BACKGROUND: The incidence of melanoma has been steadily rising in past decades. Although it accounts for only 3% of all skin cancers, it is responsible for 75% of deaths. OBJECTIVE: to describe the epidemiological aspects of melanoma in a university hospital setting over a period of 20 years. METHODS: A total of 166 patients were analyzed between January 1990 and January 2010 for clinical and histological variables and correlations between them. A 5% level of significance was adopted. RESULTS: The majority of patients were Caucasians (74%), females (61%), with a mean age at diagnosis of 55. The predominant histological type was lentigo maligna/lentigo maligna melanoma (35.7%) and the head and neck was the most affected site (30.7%). Among non-Caucasians, the acral region was the most affected. Most tumors were in situ (41.1%). Growth of the lesion was the most frequent complaint (58.1%) and bleeding was most frequently associated with melanomas with a depth > 4mm. There were seven deaths (4.2%), with a high risk among men, non-Caucasians and those under 20 years of age, with a Breslow's depth > 2mm, with lentiginous acral melanoma and with a history of growth and bleeding. CONCLUSIONS: Our sample differs from most of the studies in the predominant location (head and neck), histological type (lentigo maligna/ lentigo maligna melanoma) and a major risk of death under the age of 20, which could be with a reflex of regional variation. Broader studies are necessary for validation of the results.